1999
DOI: 10.1562/0031-8655(1999)069<0218:peoeic>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic Effects of Hypericum Extract in Cultures of Human Keratinocytes Compared with Those of Psoralen

Abstract: Extracts of Hypericum perforatum (St. John's wort) are used in the treatment of depression. They contain the plant pigment hypericin and hypericin derivates. These compounds have light-dependent activities. In order to estimate the potential risk of phototoxic skin damage during antidepressive therapy, we investigated the phototoxic activity of hypericin extract using cultures of human keratinocytes and compared it with the effect of the well-known phototoxic agent psoralen. The absorbance spectrum of our Hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…This cell line was however an immortalised line [31]. This initial study was followed by Bernd et al who reported on the cytotoxic effect of a hypericum extract on cultures of human keratinocytes [32]. Similarly, this group used an immortal keratinocyte cell line (HaCaT).…”
Section: Introductionmentioning
confidence: 99%
“…This cell line was however an immortalised line [31]. This initial study was followed by Bernd et al who reported on the cytotoxic effect of a hypericum extract on cultures of human keratinocytes [32]. Similarly, this group used an immortal keratinocyte cell line (HaCaT).…”
Section: Introductionmentioning
confidence: 99%
“…[13] Its most specific ingredients, naphthodianthrones hypericin and pseudohypericin, have both been shown to produce singlet oxygen by photooxidative reaction in cell cultures. [14][15][16][17][18] Singlet oxygen is the most likely cause of the observed phototoxicity in animals. [19] Glutathione S-transferases (GSTs) contribute to the cellular defense system against oxidative stress by their peroxidase activity, and by detoxifying xenobiotics, which serve as cofactors in radical formation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, St Johns wort is an effective and well tolerated treatment for mild to moderate depression and is generally safe as stand-alone treatment, however, it can induce adverse outcomes when used together with medications such as digoxin, warfarin or midazolam due to pharmacokinetic interactions [22]. It can also induce phototoxic skin reactions when used in high doses due to the presence of a naturally occurring pigment, hypericin [23].…”
Section: Safety Issuesmentioning
confidence: 99%